Proses Produksi Program Radio dan Televisi Berbasis Kreativitas serta Pemasaran Media di Indonesia - Winda Kustiawan; Bagas Ilham Pratama; Wasnita Waruwu; Fazira Astri; Fahira Shalsabila Batubara (Lembaga Pengembangan Kinerja Dosen, 2026)
This research discusses the production process of radio and television programs in Indonesia that is based on creativity and its relationship with media marketing strategies in responding to the dynamics of the contemporary broadcasting industry. Technological developments, changes in audience behavior, and increasing competition among media organizations require broadcasters to produce content that is innovative, relevant, and commercially valuable. This research uses a qualitative descriptive approach through literature review and conceptual analysis of radio and television production practices in Indonesia. The results show that creativity plays a crucial role at every stage of production, starting from concept development, content packaging, to program distribution across multiple platforms. In addition, media marketing strategies are essential in expanding audience reach and strengthening program competitiveness, particularly through the use of digital media and media convergence. The synergy between production teams and marketing teams enables the creation of broadcast programs that are not only artistically appealing but also effective in achieving commercial objectives. This research is expected to serve as an academic and practical reference for broadcasting practitioners in developing creative, adaptive, and sustainable radio and television programs in the digital era.